2011
DOI: 10.1175/jas-d-10-05013.1
|View full text |Cite
|
Sign up to set email alerts
|

Convective Generation of Equatorial Superrotation in Planetary Atmospheres

Abstract: In rapidly rotating planetary atmospheres that are heated from below, equatorial superrotation can occur through convective generation of equatorial Rossby waves. If the heating from below is sufficiently strong that convection penetrates into the upper troposphere, then the convection generates equatorial Rossby waves, which can induce the equatorward angular momentum transport necessary for superrotation. This paper investigates the conditions under which the convective generation of equatorial Rossby waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Scott and Polvani (2007) use a forced-dissipative model with full spherical geometry and find a polar cyclone that swims around the pole, constrained by the poleward-most jet. Schneider and Liu (2009) and Liu and Schneider (2010) also find a broad polar cyclone that precesses around the pole in a spherical shell that extends in pressure to 3 bars. The model used in the present work is the first to force a polar domain with small thermal perturbations that mimic observed moist convection in size, strength, and duration, motivated by abundant observations of intense moist convection on the gas giants (Little et al 1999;Gierasch et al 2000;Li et al 2004).…”
Section: Beta Drift On Earth and Giant Planetsmentioning
confidence: 92%
“…Scott and Polvani (2007) use a forced-dissipative model with full spherical geometry and find a polar cyclone that swims around the pole, constrained by the poleward-most jet. Schneider and Liu (2009) and Liu and Schneider (2010) also find a broad polar cyclone that precesses around the pole in a spherical shell that extends in pressure to 3 bars. The model used in the present work is the first to force a polar domain with small thermal perturbations that mimic observed moist convection in size, strength, and duration, motivated by abundant observations of intense moist convection on the gas giants (Little et al 1999;Gierasch et al 2000;Li et al 2004).…”
Section: Beta Drift On Earth and Giant Planetsmentioning
confidence: 92%
“…11, increasing S r beyond S r ; 1 by decreasing D h actually weakens the superrotation. Scaling arguments relating the strength of superrotating jets to their widths and to the static stability in the equatorial region were provided and tested in Liu and Schneider (2010) and Liu and Schneider (2011).…”
Section: B Relation To Prior Workmentioning
confidence: 99%
“…This is the case in Earth's troposphere in the annual mean, and it may be the case on Uranus and Neptune, which are subrotating (Liu and Schneider 2010). Only when the baroclinically unstable region is moved into low latitudes by artificially increasing radiative heating gradients near the equator and reducing them in higher latitudes can baroclinic instability promote the onset of superrotation (Williams 2003).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Specifically, the equatorial Rossby wave-Kelvin wave structure of the Gill response to a heating generates equatorward momentum fluxes that are likely the cause of superrotation seen in models with stationary wave-like equatorial heating (e.g., Suarez and Duffy 1992;Saravanan 1993;Kraucunas and Hartmann 2005). Other studies have found that equatorial Rossby waves (e.g., Liu and Schneider 2011;Arnold et al 2012) or Kelvin waves (e.g., Iga and Matsuda 2005) play a crucial role in the generation of superrotation. In this study, we aim partly to demonstrate the need for thinking of equatorial westerly jet dynamics as distinct from the dynamics of eddy-driven midlatitude jets.…”
Section: Introductionmentioning
confidence: 98%